Novel synthesis and characterization of CuO nanomaterials: biological applications - Devi, Ayekpam Bimolini; Moirangthem, Dinesh Singh; Talukdar, Narayan Chandra; Devi, M. Damayanti; Singh, N. Rajen; Luwang, Meitram Niraj (Chinese Chemical Letters, 2014)
CuO nanoparticles were synthesized at a relatively low temperature (80 degrees C) for 2 h using polyethylene glycol-glycerol mixture which acts as a capping agent. A detailed characterization of the synthesized nanomaterials were performed utilizing X-ray diffraction (XRD), infra-red spectroscopy (IR), thermogravimetric analysis (TGA-DTA), transmission electron microscopy (TEM), photoluminescence (PL) by studying its crystalline phase, vibrational mode, thermal analysis, morphology and photoluminescence properties. The effect of annealing on the as-prepared nanoparticles were studied and compared with their corresponding bulk counterpart. The synthesized nanoparticles have been screened for in vitro cytotoxicity (IC50) studies against the human cervical adenocarcinoma cell line (HeLa) using MTT assay methods. The as-prepared nanoparticle inhibits the proliferation of this HeLa cell. The standard disc diffusion method has been used to study the antibacterial activity of the samples against the human pathogenic bacteria Escherichia coli (MTCC 729), Proteus mirabilis (MTCC 425) and Klebsiella pneumoniae subsp. pneumoniae (MTCC 432). The results have been compared with the positive control antibiotic gentamycin. The synthesized nanoparticles would provide a potential alternative to antibiotics for controlling some of the microorganisms causing urolithiasis. (C) 2014 Meitram Niraj Luwang. Published by Elsevier B.V. on behalf of Chinese Chemical Society. All rights reserved.
Keywords: Annealing; Antibacterials; CuO nanoparticles; Cytotoxicity; HeLa cell lines

Precursor-dependent heteroatom diversity in luminescent carbon quantum dots: their impact on physicochemical properties and free radical scavenging and antibacterial activities - Konwar, Pollab Mohan; Devi, Suman; Pandey, Satish Kumar; Devi, Khomdram Sandhyarani; Devi, Ayekpam Bimolini; Luwang, Meitram Niraj (Langmuir, 2025)
The fabrication of a multifunctional carbon quantum dot (CQD) from a novel carbon source is still continuing to be demanding and fascinating. The carbon precursor plays a crucial role in developing any particular properties of a CQD to suit a specific application. In this study, green (Rhus chinensis fruits) as well as chemical-based (ascorbic acid and urea) carbon sources were used for the fabrication of CQDs using a simple, cost-effective, and eco-friendly method. The various physicochemical and optical properties of R. chinensis fruit-derived CQD (CQD-RCF) and urea-assisted ascorbic acid-derived CQD (CQD-AAU) were thoroughly investigated by using multiple characterization techniques such as XRD, TEM, HR-TEM, Raman, XPS, FT-IR, UV-vis, PL, and zeta potential. The synthesized CQDs were screened for antioxidant properties by a DPPH assay and antibacterial activity by the agar tip-well method. Both of these synthesized CQDs exhibited a variety of dissimilarities regarding their heteroatom compositions and surface functional groups, which subsequently led to an enhanced DPPH radical scavenging efficacy of CQD-AAU and a declared antibacterial efficacy of CQD-RCF. Therefore, the outcome of this study shows that the physicochemical properties and functionalities of CQDs are influenced by the chemical composition of the precursor material.